2000
DOI: 10.1149/1.1393552
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Equilibrium Hydrogen Pressure and Exchange Current for the Hydrogen Electrode Reaction at MmNi[sub 3.9−x]Mn[sub 0.4]Al[sub x]Co[sub 0.7] Alloy Electrodes

Abstract: Nickel-metal hydride (Ni-MH) batteries have attracted significant attention during the last decade because of their applications in consumer electronics, electric vehicles (EVs), and hybrid electric vehicles (HEVs). Research and development of the negative electrode materials are, however, still essential for further improvement of energy density, power density, and rate capability. 1,2 The exchange current (density), I 0 , for the hydrogen electrode reaction is one of the most important parameters for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
(54 reference statements)
3
15
0
1
Order By: Relevance
“…6A ͑curve a͒ as a function of equilibrium potential of the MH electrode, agrees well with the experimental and theoretical results reported before by Notten et al 14 and Senoh et al 15 for AB 5 -type materials. ␣ and ⌸ ca are calculated to be 0.27 and 0.545 eV, respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6A ͑curve a͒ as a function of equilibrium potential of the MH electrode, agrees well with the experimental and theoretical results reported before by Notten et al 14 and Senoh et al 15 for AB 5 -type materials. ␣ and ⌸ ca are calculated to be 0.27 and 0.545 eV, respectively.…”
Section: Resultssupporting
confidence: 92%
“…The charge-transfer coefficient ␣ was 0.35, which is quite close to the values ͑0.4-0.6͒ reported in Ref. 15. The potential barrier ⌸ ca that the system has to overcome to facilitate the chargetransfer reactions ͑Eq.…”
Section: Resultssupporting
confidence: 84%
“…The results are listed in Table I and are given as gravimetrical storage capacity in both ͓mAh/g͔ and ͓wt % H͔. The measured hy- 4,18 If the charging curves are compared, measured when hydrogenating the thin films for the first and second time, other interesting facts come to light ͓see Fig. 2-5, curves ͑a͒ and ͑d͔͒.…”
Section: Resultsmentioning
confidence: 99%
“…4 Recently, Notten et al showed that MgSc compounds exhibit very high storage capacities of up to six times that of the mischmetal-based materials. [5][6][7] Although this material can reversibly store a large amount of hydrogen, the main drawback is the very high cost of Sc.…”
mentioning
confidence: 99%
“…Theoretical model energy storage density and can be operated at high current densities and low temperatures. The NiMH battery consists of two electrodes immersed of the NiCd battery [1,2]. This makes these two different in an alkaline electrolyte, which provides ionic conducbattery systems very compatible.…”
Section: Introductionmentioning
confidence: 99%